Proposal of a performance management model for industrial clusters: Theoretical model and a case study - Lima, Rafael H. P.; Carpinetti, Luiz C. R.; Galdamez, Edwin V. C.; De Oliveira, Otavio Jose [UNESP] (My University, 2010)
In this article we propose a theoretical management model to assist governance agencies of industrial clusters in the management of collaborative initiatives as well as its own operations. The model focuses on the planning and execution of collective improvement initiatives. Strategic planning and performance measurement are used to define and manage initiatives. After a literature review on industrial clusters and the description of the model, a case study from a Brazilian industrial cluster is presented to evaluate how the work performed by the governance agency fit in the activities foreseen in the model and to discuss the appropriateness of the model for performance management.
Keywords: Industrial clusters; Management model; Performance management